Long-term health outcomes from inbreeding in a historical Swedish population: longevity, fertility, and impairments - Erling Häggström Gunfridsson; Lotta Vikström (Taylor & Francis Group, 2024)
Background Inbreeding, arising from consanguinity between related parents, has been observed to impact the health of individuals, typically attributed to biological factors. Nevertheless, these effects may be influenced by the social and environmental conditions. The prevalence of consanguineous marriages increased in certain parts of Sweden after it became legal in 1844, which offers a unique opportunity to study and understand the effects of inbreeding on health.Aim The objective of this study is to explore the potential impact of inbreeding on the longevity, fertility, and impairments of individuals born in the Skellefteå region, Sweden, between 1890 and 1905, with a follow-up period extending until 1950.Subjects and methods The level of inbreeding is calculated using micro-level parish register data and related to longevity, fertility, and impairments using regression analysis.Results Inbreeding is shown to be associated with longevity, fertility, and impairments. It seems to affect the risk of stillbirth and impairments and male longevity and fertility.Conclusion Inbreeding seems to have had a detrimental effect on some health outcomes in this historical population under study.